The Effect Of Transformational Leadership And Work Motivation On Employee Performance Of The Central Statistics Agency (BPS) Of South Bengkulu Regency - Alnando, Fitro; Gayatri , Ida Ayu Made Er Meytha; Nurzam, Nurzam (Utami Publisher, 2025)
The type of research used in this study was quantitative descriptive. The sample in this study was 30 people with the sampling technique in this study being total sampling. Data collection techniques were observation, questionnaires and documentation. The data analysis technique used in this study was quantitative descriptive. The results showed that there was a significant influence between transformational leadership on employee performance with a t-count value of 2.745> 1.70562 and a sig a value = 0.011 <0.050; there was a significant influence between work motivation on employee performance with a t-count value of 4.688> 1.70562 and a sig a value = 0.000 <0.050. Simultaneously, transformational leadership variables and work motivation on employee performance at the South Bengkulu Central Statistics Agency with an Fcount value of 15,422> 3.35 with a significance value smaller than the probability of 5%, namely 0.000.